The Quality of Education from Islamic Perspective Analysis of The Merdeka Belajar Curriculum in Facing The Society 5.0 Era - Rochmat, Cecep Sobar; Yoranita, Angelica Silfana Prisca Yoranita; Prihatini, Mispullah; Wibawa, Bagus Asri (Jurnal Tarbiyatuna, 2023)
VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) is one of the difficulties faced by society in the 5.0 era, which is a combination of the virtual world and the physical world. Therefore, the global community must adapt quickly and be malleable to face the changes. The 4Cs (critical thinking, creativity, collaboration and communication) are essential 21st century skills. To keep up with global trends, the Indonesian government has implemented a curriculum that emphasizes individual initiative and responsibility. This study aims at analyzing the Merdeka Belajar curriculum by using quality education in Islamic perspective. Merdeka Belajar (Freedom to learn) is the latest government policy related to the education curriculum, and hence, islamic perspective - based analysis needs to be conducted to see how this concept of Merdeka Belajar is in Islamic education. This study was a descriptive qualitative study by using literature studies to collect the data. The results showed that the government's Merdeka Belajar curriculum system can accommodate the skills needed for the society 5.0 era. The concepts and programs of Merdeka Belajar can improve critical and creative thinking skills, and develop communication and collaboration skills as well. Merdeka Belajar directs students to be able to compete globally. Holistic Islamic education, however, does not only appreciate the importance of building skills, but also creates learning that glorifies knowledge without reducing Islamic values. Therefore, the independent current curriculum applied needs to be adjusted to keep in line with both the values and the 21st century skill development.